Energy security and renewable energy potential of the EU and Ukraine in terms of the Russia’s aggression - Yakymenko, Igor; Bublienko, Natalia; Salavor, Oksana; Nychyk, Oksana; Shapovalov, Yevhenii; Henschel, Denis (My University, 2025)
Russia’s full-scale invasion of Ukraine in February 2022 and the subsequent energy crisis throughout Europe revealed a dangerous dependence of European countries on Russian energy resources. This resulted in a crucial change in energy strategy of the European Union (EU). Following the REPowerEU strategy, the European Union already decreased Russian gas import by two-thirds (from 45 % to 15 % of total natural gas import) and plans totally refuse Russian energy supplies «well before the end of the decade». The EU strategy on complete replacement of Russian energy supplies and accelerating implementation of renewable sources of energy is challenging right now but crucial for Europe’s long-term energy security. The EU’s current binding target to achieve 42,5 % of renewable energy sources in the total energy mix by 2030 is in line with the European Green Deal strategy and works on the independence of the EU from Russian energy resources. Ukraine is currently withstanding the worst of the war, including thousands of deaths, millions of refugees, occupied territories, and destroyed infrastructure. National energy security is just one of many challenges facing the country. Following the EU’s strategy, Ukraine urgently needs to transform its energy sector in a sustainable manner. Ukraine’s current plan to achieve 27 % renewables in total energy production by 2030, while less ambitious than the EU’s goal, is still a compelling strategy given the country’s wartime situation. The country can and should rely heavily on renewable energy sources, including solar and wind generation. Biogas and biomethane production can also play a significant role in replacing natural gas in Ukraine, given the country’s vast agricultural potential. Along with a radical increase in energy efficiency, this will transform Ukraine’s energy sector into a sustainable and secure one. Повномасштабне вторгнення Росії в Україну в лютому 2022 року та подальша енергетична криза по всій Європі виявили небезпечну залежність європейських країн від російських енергетичних ресурсів. Російське вторгнення в Україну призвело до кардинальної зміни енергетичної стратегії Європейського Союзу (ЄС). Реалізуючи стратегією REPowerEU, ЄС вже скоротив імпорт російського газу на дві третини (з 45 % до 15 % загального імпорту газу у ЄС) та планує повністю відмовитися від російських енергетичних поставок «задовго до кінця десятиліття». Стратегія ЄС щодо повного заміщення російських енергетичних поставок та прискорення впровадження відновлюваних джерел енергії є складною на даний момент, але має вирішальне значення для довгострокової енергетичної безпеки Європи. Поточні зобов’язуючі цілі ЄС щодо досягнення 42,5 % відновлюваних джерел енергії в загальному енергетичному балансі до 2030 року відповідають стратегії Європейського зеленого курсу та спрямовані на незалежність ЄС від російських енергетичних ресурсів. Наразі Україна несе основний тягар війни, включаючи тисячі смертей, мільйони біженців, окуповані території та зруйновану інфраструктуру. Національна енергетична безпека – це лише один із багатьох викликів, що стоять перед країною. Дотримуючись стратегії ЄС, Україні терміново потрібно трансформувати свій енергетичний сектор у сталий спосіб. Поточний план України щодо досягнення 27 % відновлюваних джерел енергії в загальному виробництві енергії до 2030 року, хоча й менш амбітний, ніж ціль ЄС, але є переконливою стратегією, враховуючи воєнну ситуацію в країні. Країна може і повинна значною мірою покладатися на відновлювані джерела енергії, включаючи сонячну та вітрову генерацію. Виробництво біогазу та біометану також може відігравати значну роль у заміні природного газу в Україні, враховуючи величезний сільськогосподарський потенціал країни. Поряд із суттєвим підвищенням енергоефективності, це перетворить енергетичний сектор України на сталий та безпечний.
Keywords: кафедра екології та екоменеджменту; energy security; sustainable development; renewables; energy resources; Russia’s war in Ukraine; енергетична безпека; сталий розвиток; відновлювані джерела енергії; енергетичні ресурси; війна Росії в Україні